Buy-Now-Pay-Later (BNPL) dan Perilaku Konsumtif Generasi Muda di Indonesia - Novita Novita; Lelly Christin; Janny Rowena (Value : Jurnal Manajemen dan Akuntansi, 2026)
The growth of e-commerce, social media, and Buy Now Pay Later (BNPL) services has transformed the consumption patterns of Indonesia’s younger generation. The ease of access to digital credit which is integrated with various shopping platforms and social media increases the potential for impulse buying, which can develop into compulsive spending behavior. This study aims to analyze the effect of social media influence on the consumptive behavior of PayLater users in Indonesia, taking into account the mediating role of impulse buying and the moderating role of financial literacy. The study employs a quantitative approach through a survey of 170 PayLater users from the Millennial and Generation Z cohorts. The results indicate that social media influence affects impulse buying but does not have a direct effect on consumptive behavior. Conversely, impulse buying influences consumptive behavior and fully mediates the relationship between social media influence and consumptive behavior. Financial literacy was found to weaken the influence of impulse buying on consumptive behavior. These findings suggest that the consumptive behavior of PayLater users is more influenced by psychological drives in the form of impulsive buying, while financial literacy acts as a protective factor in making more rational consumption decisions.